The forgotten ones : a case study of the obstacles that prevent meaningful participation in democratic governance of farm women in the greater Stellenbosch Area, Ceres & Rawsonville - Saal, Querida Shahida (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.